2017
DOI: 10.1037/edu0000179
|View full text |Cite
|
Sign up to set email alerts
|

Language-independent and language-specific aspects of early literacy: An evaluation of the common underlying proficiency model.

Abstract: According to the common underlying proficiency model (Cummins, 1981), as children acquire academic knowledge and skills in their first language, they also acquire language-independent information about those skills that can be applied when learning a second language. The purpose of this study was to evaluate the relevance of the common underlying proficiency model for the early literacy skills of Spanish-speaking language-minority children using confirmatory factor analysis. Eight hundred fifty-eight Spanish-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…They propose to make programs more culturally valid-that is, consistent with parents' values and behaviors. Such suggestions reflect a wider movement away from a deficit view toward a perspective that builds on the knowledge and resources available in families (Irvine & Larson, 2007;Street, 1995), as elaborated in concepts such as "funds of knowledge" (González al., 2005;Moll et al, 1992) and "community culture wealth" (Yosso, 2005). The assumption is that using family knowledge and resources can play an important role in children's academic achievements, as was corroborated by Rios-Aguilar (2010).…”
Section: Effects Of Family Literacy Programs: Previous Meta-analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…They propose to make programs more culturally valid-that is, consistent with parents' values and behaviors. Such suggestions reflect a wider movement away from a deficit view toward a perspective that builds on the knowledge and resources available in families (Irvine & Larson, 2007;Street, 1995), as elaborated in concepts such as "funds of knowledge" (González al., 2005;Moll et al, 1992) and "community culture wealth" (Yosso, 2005). The assumption is that using family knowledge and resources can play an important role in children's academic achievements, as was corroborated by Rios-Aguilar (2010).…”
Section: Effects Of Family Literacy Programs: Previous Meta-analysesmentioning
confidence: 99%
“…At the same time, several studies have shown substantial variability in how children's home literacy environments (HLEs) are shaped, not only between, but also within SES groups (Auerbach, 2001;Lynch, 2009;van Steensel, 2006). Using refined conceptualizations of the HLE, such studies suggest that low-SES families do provide opportunities for literacy development, but in different ways (González et al, 2005). Consequently, it is recommended that FLPs adhere to the resources available in these families.…”
mentioning
confidence: 99%
“…Therefore, linguistic transfer through a CUP may not be the source of successful interdependence in language learning. Nevertheless, Goodrich and Lonigan (2017) note that the lack of a CUP does not rule out all types of transfer of language skills; prior evidence suggests that children transfer some word-specific information across languages (Goodrich et al, 2016). Summarizing the results of available studies conducted with young Spanish-English bilinguals, Patterson and Pearson (2004) conclude that there is no consistent evidence that knowing a word in L1 will make it easier to learn it in L2.…”
Section: Linguistic Interdependencementioning
confidence: 99%
“…For this reason, a significant proportion of DLLs' early vocabularies may be comprised of words known in one or the other language, but not both (Peña, Bedore, & Zlatic-Giunta, 2002;Rinker, Budde-Spengler, & Sachse, 2017). Moreover, a large body of work suggests that vocabulary growth in one language may be more strongly linked with properties of input in that language than the other, at least in the early stages of development (Goodrich & Lonigan, 2017;Hoff et al, 2012).…”
Section: Vocabularymentioning
confidence: 99%
“…Although grammar development is undoubtedly linked with exposure to each language (Marchman, Mart ınez-Sussmann, & Dale, 2004), children may also generate abstract grammatical representations by detecting distributional regularities in the input across languages (Goodrich & Lonigan, 2017;Messenger & Fisher, 2018). Thus, in comparison with vocabulary, the domain of grammar may be relatively language-independent.…”
Section: Grammarmentioning
confidence: 99%